Decrypting the communication between microbes and the intestinal mucosa—A brief review on Pathogénie Microbienne Moléculaire's latest research. (30th October 2019) - Stedman, Aline; Brunner, Katja; Nigro, Giulia
Abstract: Over the past 10 years, the "Pathogénie Microbienne Moléculaire" unit of Professor Philippe Sansonetti has studied the molecular cross talk between the intestinal microbiota and the gut epithelium, aiming to better understand how this mutualistic symbiosis delineates homoeostasis and, when perturbed, prompts pathology. To do so, the unit has manipulated both bacterial and epithelial cells, and used cutting‐edge technology. More recently, the lab has turned its focus also on studying the intestinal crypt and more specifically the intestinal stem cell for their role in epithelial regeneration and long‐term epithelium renewal. Here, we provide a brief review summarising recent results obtained from the lab, with particular focus on the intestinal crypt.